Renewable energy from solar, biomass and biofuels resources - SAHAM IBARHIAM (2021)
In the current study, the waste stones and rachis obtained from Barhee and Medjool dates palm trees were characterized on a laboratory scale and their potential as biomass feedstock were investigated. The proximate, ultimate, structure/composition and thermo-gravimetric analysis experiments were conducted to characterize the selected biomass materials. The results showed that the Medjool and Barhee stones are a promising biomass feedstock as they have high volatile and fixed carbon contents with low ash content. Moreover, they have high carbon and nitrogen contents with a very high cellulose contents reaching up to 66% in the case of Barhee stones. The thermo-gravimetric analysis showed that the decomposition of Barhee and Medjool stones can be completed below 420 °C; while it can be completed below 360 °C for Barhee and Medjool rachis under thermo-gravimetric pyrolysis analysis. Based on the TGA results obtained, slow pyrolysis experiments for the stones and rachis feedstock materials were conducted. Among the four slow pyrolysis trials, maximum yield for bio-oil of 21.54% was achieved when Barhee rachis was used, while Medjool rachis produced the least value. Characterization and analysis of the bio-oil extracted from the pyrolysis experiments showed the superiority of the bio-oil from Barhee stone as it has the highest heating value. The gas chromatography mass spectrometry analysis showed that phenol, furfural and benzoic acid are the main components of the bio-oil obtained from the date palm rachis samples while d-allose, furfural, 5-methyl 2-furancarboxaldehyde, and dodecanoic acid are the main components of the bio-oil extracted from the date palm stones. The opportunities of exploitation of renewable energy with solar, biomass and biofuels resources in the Middle East, are also reviewed in detail in this work. The techno-economic analysis for the concentrating solar power plants installed in the Middle East showed promising potential from the economic and technical point of view.